2012
DOI: 10.1128/aem.01059-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Inactivation of Murine Norovirus, Human Adenovirus, and Human JC Polyomavirus by Chlorine in Seawater

Abstract: cViruses excreted by humans affect the commercial and recreational use of coastal water. Shellfish produced in contaminated waters have been linked to many episodes and outbreaks of viral gastroenteritis, as well as other food-borne diseases worldwide. The risk can be reduced by appropriate treatment following harvesting and by depuration. The kinetics of inactivation of murine norovirus 1 and human adenovirus 2 in natural and artificial seawater by free available chlorine was studied by quantifying genomic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…; Sauerbrei and Wutzler ; de Abreu Corrêa et al . ). Due to these characteristics, HAdV has been described together with JC polyomavirus (JCPyV) as an indicator of human viral contamination (Bofill‐Mas et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Sauerbrei and Wutzler ; de Abreu Corrêa et al . ). Due to these characteristics, HAdV has been described together with JC polyomavirus (JCPyV) as an indicator of human viral contamination (Bofill‐Mas et al .…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, pretreatment of samples with RNase prior to RT-qPCR is not likely to account for particles that remain intact but have lost HBGA or aptamer binding functionality. It has generally been observed that RNase pretreatment underestimates reductions observed by plaque assay (39, 40). Specifically, one study that directly compared a receptor (cell binding)-based assay to RNase pretreatment for murine norovirus subjected to heat found that cell binding more closely predicted viral reduction than did RNase treatment prior to RT-qPCR (41).…”
Section: Discussionmentioning
confidence: 99%
“…HAdVs are large double-stranded DNA pathogens ( Table 1) that cause a wide variety of infections and are widely prevalent in the environment (19)(20)(21). They have been suggested to be indicators of human fecal contamination and have been included in many disinfection studies as a process control (22)(23)(24)(25)(26)(27). From our data, ϳ3-log inactivation would occur at a fluence of 1.34 kJ/cm 2 ( HAdV ϭ 4.58 Ϯ 0.26 cm 2 /kJ) (Fig.…”
Section: Development Of An Experimental Setup For the Study Of Sodismentioning
confidence: 99%